IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PENGELOLAAN ZAKAT DI BAZNAS DAN LAZ DPU KUTAI TIMUR: Indonesia - Firdaus, Firdaus (At-Tawazun, Jurnal Ekonomi Syariah, 2022)
Zakat management institutions are institutions that manage funds from the community. Therefore, it needs to be managed professionally. One system that is used as a reference in measuring the performance of the institution is to implement the principles of good corporate governance. Good corporate governance is a set of systems that regulate and control an institution in order to be able to create a management work pattern that is transparent, accountable, clean and professional.This research use desciptive qualitative approach. The results showed that BAZNAS and LAZ DPU East Kutai had implemented the principles of good corporate governance in zakat management by providing management information, submitting reports, complying with applicable regulations, carrying out their functions and duties independently, and treating the community the same way in receiving services and information. Factors that support the implementation are government regulations and audit institutions. While the differences in implementation are seen in the provision of information, the responsibility for submitting financial reports, compliance with regulations, the establishment of institutions, and the provision of information and services to the public.